Electrospun Nanofibers from Durian Rind-Derived Nanocellulose: Influence of Tween 20 and Tween 80 on Morphology and Structure for Livestock Semen Preservation - Azima Azmi; Ainaa Abdul Kahar; Nur Sabrina Wahab; Muhammad Zaidi Abu Bakar; Mariah Batrisyia Muhammad; Ainu Husna M S Suhaim; Julie Marzlinda Mohd Razak; Abdul Mu'in Hassan Basri; Shazwan Abd. Shukor; Nurul Hazwani Aminuddin Rosli; Chin Hua Chia; Shahariah Chowdhury, (International Journal of Nanoelectronics and Materials (IJNeaM), 2026)
This study explores the utilization of nanocellulose derived from durian rind as a reinforcing agent in electrospun nanofibers intended for potential use in livestock semen preservation. Nanocellulose was extracted through alkaline treatment followed by acid hydrolysis and incorporated into polyvinyl alcohol (PVA) solutions. Tween 20 and Tween 80 are selected to investigate the effect of dispersion and morphology on nanocellulose during the electrospinning process. FESEM, XRD, and FTIR were then used to characterize the electrospun nanofibers. Morphological images show that the electrospun nanofibers with Tween 80 are mostly uniform in width and surface appearance compared to those with Tween 20. Good fiber dispersion indicates that Tween 80 offers greater solution stability than Tween 20. FTIR spectra confirmed matrix bonding between polyvinyl alcohol (PVA) and nanocellulose, as well as the functional groups of both. X-ray diffraction (XRD) analysis indicated that electrospun nanofibers loaded with Tween 80 showed an elevated degree of crystallinity. This indicates the stability of the superior alignment structure. The enhanced characteristics observed in the electrospun nanofibers incorporated with Tween 80 suggest physical stability and significant barrier properties, which are key requirements for semen preservation applications. This study has demonstrated the viability of transforming agricultural by-products into valuable nanomaterials and highlighted the importance of selecting a suitable surfactant to modulate the properties of electrospun nanofibers. The data from this study show that electrospun nanofiber membranes could be promising, offering an alternative biocompatible material for semen preservation.